Analisis Perjanjian Modal Ventura Pola Bagi Hasil antara Kitab Undang-Undang Hukum Perdata dan Kompilasi Hukum Ekonomi Islam - Santoso, F. Setiawan (IAIN Salatiga, 2016)
One resolution of moral hazard in venture capital (CV) is clarity and certainty in his Covenant. This article about it by analyzing the juridical basis of the Covenant pattern for CV results within the scope of KUHPerdata and KHES of mudarabah in solving CV. With this initial exploration is expected to be able to make a donation to the religious courts in Indonesias practitioners who still recognize both the economic problems of the Sharia in the settlement that became his authority. Both views do not differ greatly in resolving issues of venture capital can even complement each other’s weaknesses in deciding the problems of venture capital